ANALYSIS OF SKILL CRITICAL THINKING STUDENTS ON LEARNING MATHEMATICS CURRICULUM 2013 CLASS V SDN 59 PEKANBARU - Cindy Rahmadani Putri (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
Critical thinking skills are very important owned, because having critical thinking skills can help us think logically in overcoming the problems we face and looking for and developing alternative solutions to those problems.This study aims to identify and describe student’s critical thinking skills in mathematics learning curriculum 2013 class V SDN 59 Pekanbaru. This research was conducted on January 22, 2020. Research subjects totaled 35 students consisting of 19 male students and 16 female students. This type of research is qualitative research. Data collection instruments in the form of test questions consisting of 5 essay questions and interview guidelines conducted on several students. The results showed 60% in the very low category, 27.5% in the low category, 8.5% in the medium category, and 2.8 in the high and very high categories. Based on the result of data analysis, it can be concluded that the critical thinking skills of studnts in learning mathematics in curriculum 2013 class V SDN 59 Pekanbaru are in the very low category